Utilization of tissue-free minimal residual disease testing in colorectal cancer patients from Asia and Middle East - Jain, Suyog; Dawood, Shaheenah; Lavingia, Viraj; Aderka, Dan; Tahover, Esther; Hsieh, Yao-Yu; Temper, Mark; Goldman, Alesya; Akasheh, Marwan AI.; Olsen, Steve; Hsing, Sandra San; Joshi, Nisarg; et al. (Frontiers in Oncology, 2024)
IntroductionThe presence of minimal residual disease (MRD) after curative-intent surgery for early-stage cancers is associated with disease recurrence. Circulating tumour deoxyribonucleic acid (ctDNA) has emerged as a promising biomarker for MRD assessment in patients with colorectal cancer (CRC) who have undergone surgery or completed adjuvant therapy. MRD tests are already available for use in clinics; however, treatment decisions following MRD results obtained in routine practice are infrequently described. MethodsIn this observational study, we report on the real-world clinical use of Guardant Reveal, a validated tissue-free MRD assay, in the first 215 consecutive patients (279 samples) with CRC tested in Asia and the Middle East. ResultsOverall, 22% of patients had ctDNA detected in their first MRD test, and the frequency of ctDNA positivity increased with increasing tumour stage. 132 samples were tested with an earlier version of Guardant Reveal, one that assessed both genomic and epigenomic features. An updated version of the assay assesses only ctDNA methylation data and was used for the remaining 147 samples. In patients with stage II CRC, 71% of tests were ordered within 12 weeks after tumour resection, while for patients with stage III disease, 69% of tests were ordered after completion of all curative-intent treatment. DiscussionClinical cases utilizing tissue-free MRD assessment are described.